Analysis and Prediction of the Occurrence of an Earthquake Using ARIMA and Statistical Tests - Kumoro, Rabbani Nur; Fattima, Audrey Shafira; Susatyo, William Hilmy; Fudholi, Dzikri Rahadian (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2024)
Earthquakes present significant risks to both human safety and infrastructure, emphasizing the need for precise prediction models to minimize their adverse effects. This study seeks to tackle the challenge of accurately forecasting the occurrence time of earthquakes by utilizing the LANL Earthquake dataset, which comprises seismic signals from a laboratory model emulating tectonic faults. In this study, we employed the ARIMA model and compared it with Linear Regression to predict earthquake occurrences. Our findings demonstrate that the ARIMA (1,1,1) model surpasses other models, achieving the lowest MAE of 0.110628. The validity of the model's assumptions is confirmed through the Ljung-Box and Jarque-Bera tests, which verify the absence of autocorrelation and the normal distribution of residuals, respectively.